Các yếu tố ảnh hưởng đến quyết định chọn trường đại học của sinh viên năm thứ nhất: Nghiên cứu trường hợp tại Đại học Trà Vinh - Nguyễn Minh Hòa, Nguyễn Minh Hòa; Nguyễn Thành, Gia; Phạm Hiệp Cường, Phạm Hiệp Cường (Tạp chí Giáo dục, 2026)
University choice is shaped by a range of factors related to students, higher education institutions, and the broader social environment. This study examined the factors influencing first-year students’ decision to choose Tra Vinh University and analysed differences by gender, place of residence, and field of study. A quantitative cross-sectional design was employed with 3,306 first-year students enrolled in the 2025-2026 academic year. Data were collected using a 26-item questionnaire and analysed through descriptive statistics, independent-samples t tests, analysis of variance, Pearson correlation, and multiple linear regression. The results indicated that institutional conditions and reputation, employment opportunities, and communication activities were positive statistical predictors of university choice, with institutional conditions and reputation emerging as the strongest predictor. Gender differences were found only in the evaluation of employment opportunities, whereas differences by place of residence were observed across all study variables. Differences by field of study were identified in institutional conditions and reputation, employment opportunities, and interpersonal factors. The study adds empirical evidence on university choice in the Mekong Delta and provides a reference for student recruitment, institutional communication, and career guidance in higher education institutions.